Perspectives on the α5 nicotinic acetylcholine receptor in lung cancer progression - Cai, Jiaying; Wang, Jingting; Wang, Zengping; Wang, Jing; Jia, Yanfei; Ma, Xiaoli (Frontiers in Cell and Developmental Biology, 2025)
Nicotinic acetylcholine receptors (nAChRs) are widely expressed in a variety of cell types and are involved in multiple physiological regulatory mechanisms in cells, tissues and systems. Increasing evidence suggests that the α5 nicotinic acetylcholine receptor (α5-nAChR), encoded by the CHRNA5 gene, is one of a key mediator involved in lung cancer development and immune responses. Several studies have shown that it is a regulator that stimulates processes via various signaling pathways, including STAT3 in lung cancer. In addition, α5-nAChR has a profound effect on lung immune response through multiple immune-related factor pathways. In this review, we focus on the perspectives on α5-nAChR in lung cancer progression, which indicates that targeting α5-nAChR could provide novel anticancer and immune therapy strategies for lung cancer.